1966
DOI: 10.3406/bulmi.1966.5951
|View full text |Cite
|
Sign up to set email alerts
|

Étude du polymorphisme des sesquioxydes de terres rares à haute température

Abstract: Les courbes obtenues lors de l'analyse thermique des sesquioxydes de terres rares à haute température présentent, entre 1 800° et 2 400° C, un certain nombre d'anomalies susceptibles de correspondre à des changements de forme cristalline. L'étude aux rayons X à haute température de ces phénomènes a permis de confirmer cette hypothèse et de mettre en évidence deux formes cristallines nouvelles. Tous les sesquioxydes de terres rares, à l'exception probablement du dernier terme de la série, Lu₂O₃, cristallisent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1968
1968
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…In general on going from La to Lu, the structure of RE 2 O 3 changes from A-type to B-type to C-type. Foex and Traverse [24] have reported that the stability of C-type modification increases on decreasing the RE 3+ ionic size. In fact, Lu 2 O 3 , which is C-type, does not undergo any phase transition as it directly melts.…”
Section: Resultsmentioning
confidence: 98%
“…In general on going from La to Lu, the structure of RE 2 O 3 changes from A-type to B-type to C-type. Foex and Traverse [24] have reported that the stability of C-type modification increases on decreasing the RE 3+ ionic size. In fact, Lu 2 O 3 , which is C-type, does not undergo any phase transition as it directly melts.…”
Section: Resultsmentioning
confidence: 98%
“…Owing to the high transition temperature (>2000°C), structural studies on these materials remain challenging and phase stabilities are difficult to verify. For Sm 2 O 3 and Gd 2 O 3 , a hexagonal ( H phase) to cubic ( X phase, Im ‐3 m ) phase transition has been reported at 2250° and 2360°C 37 . Therefore the presence of a cubic fluorite phase at high temperature is possible.…”
Section: Discussionmentioning
confidence: 99%
“…For Sm 2 O 3 and Gd 2 O 3 , a hexagonal (H phase) to cubic (X phase, Im-3m) phase transition has been reported at 22501 and 23601C. 37 Therefore the presence of a cubic fluorite phase at high temperature is possible. (4) The interaction parameters of both ZrO 2 -REO 1.5 and HfO 2 -REO 1.5 are strongly negative, lying between À107.5 and À89.2 kJ/mol for ZrO 2 -REO 1.5 and between À138.1 and À93.7 kJ/mol for HfO 2 -REO 1.5 solid solutions.…”
Section: July 2007mentioning
confidence: 99%
“…Additional reaction components can help to transform the sesquioxides during the temperature treatment. For example, Foex et al achieved a transformation from the C-type to the B-type structure by adding some lime [33], or by offering support with oxides like CaO and SrO [37].…”
Section: B-ho 2 Omentioning
confidence: 99%